Dowry in the light of the purposes of Sharia according to Ibn Ashour - Mar'ati Sholihah; Imron Rosyadi; Mohammad Abdul Kholiq Hasan (Universitas Darussalam Gontor, 2022)
This research deals with a topic about a woman's dowry in the light of the legitimate purposes of one of the intentional scholars, Sheikh Ibn Ashour. The research clarifies the woman's dowry, her portrayal, and the purposes of Sharia according to Ibn Ashour, then analyzes and achieves them in the three interests. And this research has tried to answer problems, the most important of which is the nature of the woman's dowry according to Ibn Ashour and how to achieve it in the three interests? This research aims to know the dowry of a woman according to Ibn Ashour. The method of this research is an analytical desk research by depicting the woman’s alimony and analyzing it according to the opinions of the legitimate purposes of Sheikh Ibn Ashour and some scholars, and as a result: that the necessary purposes of the woman’s dowry are: preserving lineage, and it is a general purpose of marriage, which is the reason for the necessity of this alimony, so the woman assumes her responsibility In the marriage in which the offspring is preserved, then the soul is preserved, because the woman is imprisoned from the benefits of her husband and she is forbidden from disposing of his rights except with his permission, so she must be provided with her provision and her maintenance, and the protection of the woman from the deadly work is the maintenance of the poor woman. Then he preserves the religion while she finds a woman who can guarantee her so that she does not go out to forbidden actions, and differentiate between adultery, incest, and cheating. Al-Tahsiniyyah is: the woman’s maintenance while she is rich, and the achievement of the woman’s respect for the authority of the man. Key words: dowry, purposes of Sharia, three interests, Ibn Ashour